Metamorphic testing for cybersecurity - Chen, Tsong Yueh; Kuo, Fei-Ching; Ma, Wenjuan; Susilo, Willy; Towey, Dave; Voas, Jeffrey; Zhou, Zhi Quan (Institute of Electrical and Electronics Engineers, 2016)
Metamorphic testing (MT) can enhance security testing by providing an alternative to using a testing oracle, which is often unavailable or impractical. The authors report how MT detected previously unknown bugs in real-world critical applications such as code obfuscators, giving evidence that software testing requires diverse perspectives to achieve greater cybersecurity.